The Plebeian Republic : The Huanta Rebellion and the Making of the Peruvian State, 1820-1850 - Mendez G., Cecilia (Book collections on Project MUSE., 2005)
Examines the politics of a 19th c. peasant revolt in Peru, looking at the organization and practice of government by the rebels to examine what a largely illiterate population understood by terms such as "nation" and showing the rebellion's sign.